Identification and Quantitation of Volatile Organic Compounds in Poly(methyl methacrylate) Kitchen Utensils by Headspace Gas Chromatography/Mass Spectrometry. (27th November 2019) - Ohno, Hiroyuki; Mutsuga, Motoh; Kawamura, Yoko
Abstract: A headspace GC/MS method was developed for identification and quantitation of residual volatile organic compounds in poly(methyl methacrylate) (PMMA) kitchen utensils. A sample was cut into small pieces, then N, N -dimethylacetamide was added in a headspace vial and sealed. After storing for more than 1 day at room temperature, the vial was incubated for 1 h at 90°C, and the headspace gas was analyzed by GC/MS. In 24 PMMA kitchen utensils, 16 volatile organic compounds including methyl methacrylate, methyl acrylate, toluene, 2-methyl-1-butene, 2-methyl-2-butene, 2-methylpropanal, methyl propionate, methyl isobutyrate, trans -3-heptene, heptane, cis -3-heptene, trans -2-heptene, cis -2-heptene, 2, 4, 4-trimethyl-1-pentene, 2, 4, 4-trimethyl-2-pentene, and 1-octene were identified and quantitated. These 15 volatile compounds except methyl methacrylate were found for the first time in PMMA kitchen utensils. Recovery rates from spiked samples were 97.4–104.0% with CV values of 2.8–9.6%. Samples contained 190–7900 μg/g of methyl methacrylate, 26–810 μg/g of methyl acrylate, and 2–1300 μg/g of toluene; other compounds were at levels less than 100 μg/g. Methyl methacrylate was the main monomer of PMMA and methyl acrylate was a comonomer; toluene should be used as a solvent.